ISLAMIC FINANCE AND THE ROLE OF ISLAMIC INSURANCE IN IT (World Economics and Finance Bulletin, 2024)
This article reveals the role and importance of Islamic finance and Islamic insurance in it, and offers suggestions and recommendations for improving the practice of Islamic insurance in the future
Keywords: Islamic Insurance; Insurer; Insured; Reinsurer